2017
DOI: 10.9790/2402-1103014147
|View full text |Cite
|
Sign up to set email alerts
|

Vitamins, Amino Acids, Lipids and Sterols of Eggs from Three Different Birds Genotypes

Abstract: The study compared the nutritional and physical quality of whole raw and cooked eggs of birds collected from three different genotypes as well as environments,namely (Broiler chicken (Gallus gallus), quail (Coturnix coturnix japonica ) and Local chicken or indigenous (Gallus gallus domesticus 034-20.474, 0.219-0.506; 0.015-0.615; 2436.4-9683.0; 7.670-14.574; 0.883 -0.993 and 0.291-0.0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Leucine had beneficial and functional to protein structure and blood sugar level regulation which maintains a balance of insulin and glucose On the other hand, for non-essential amino acids, glutamic acid was the predominant in both quail and chicken eggs with values 14.29 and 14.16 g/100g respectively. Similar finding was obtained by Genchev, (2012) and Aletor and Famakin, (2017). Augustine et al, (2007) reported that glutamic acid had vital role for healthy brain development and function.…”
Section: Total Fatty Acids Content Of Quail and Chicken Eggssupporting
confidence: 85%
“…Leucine had beneficial and functional to protein structure and blood sugar level regulation which maintains a balance of insulin and glucose On the other hand, for non-essential amino acids, glutamic acid was the predominant in both quail and chicken eggs with values 14.29 and 14.16 g/100g respectively. Similar finding was obtained by Genchev, (2012) and Aletor and Famakin, (2017). Augustine et al, (2007) reported that glutamic acid had vital role for healthy brain development and function.…”
Section: Total Fatty Acids Content Of Quail and Chicken Eggssupporting
confidence: 85%
“…The content of essential amino acids (EAA) in the "ideal protein" was used as a reference protein in the calculation of AAS (FAO/WHO/UNU, 2007) and in quail egg protein determined after averaging the EAA content of eggs published in the scientific literature (Genchev, 2012;Aletor and Famakin, 2017;Dimkov et al, 2019;Shcherbatov and Bachinina, 2021).…”
Section: Chemical Analysismentioning
confidence: 99%
“…Much wider is the ratio published in the literature between UFA and SFA in breast meat, which reaches 2.57:1 (Khalifa et al, 2016) -2.74:1 (Mazizi et al, 2020). In the UFA group, the ratio of monounsaturated (MUFA) to polyunsaturated fatty acids (PUFA) was 1.76:1 for breast meat and 1.74:1 Note: * The ideal protein is based on the recommendations about the recommended intake of EAA in mg/1 g protein (FAO/WHO/UNU, 2007); ** The content of EAA in egg protein is based on average data on their content in quail eggs (Genchev, 2012;Aletor and Famakin, 2017;Dymkov et al, 2019;Shcherbatov and Bachinina, 2021. ) for leg meat.…”
Section: Eaa Content In Meat Gives Reliable and Accuratementioning
confidence: 99%